Neutrophil- Lymphocyte Ratio (NLR) and Platelet- Lymphocyte Ratio (PLR) as Inflammatory Markers in Preterm Birth - Izzah, Muthiah Nurul; Sumawan, Herman; Achmad, Eppy Darmadi (Indonesian Journal of Obstetrics & Gynecology Science, 2024)
Introduction: Preterm births make up roughly 16–18% of all live births in Indonesia. One of the factors that contribute to preterm birth is inflammation. The study aimed to assess the role of platelet/lymphocyte ratio (PLR) and neutrophil/lymphocyte ratio (NLR) as inflammatory markers in preterm birth. Method: This is a cross-sectional retrospective Study. Data were collected from medical records at Margono Soekarjo Hospital, January 2022-February 2023. The cohort comprised 150 participants with singleton pregnancies, ranging from 28 to less than 37 weeks of gestation, divided into three groups: preterm birth without preterm premature rupture of membranes (PPROM), preterm birth with PPROM, and threatened preterm labor (TPL). Multivariate ANOVA tests were employed for data analysis. Result: There was a statistically significant difference NLR values , notably in preterm births without PPROM compared to other groups (p value < 0.005), whereas the only difference noted in PLR values was noted between preterm births with and without PPROM. Our finding differs from that of previous studies, which indicated higher NLR values in preterm births with PPROM.Conclusion: NLR and PLR have the potential to be used as inflammatory markers indicative of heightened risk of preterm birth.Rasio Neutrofil-Limfosit (RNL) dan Rasio Platelet-Limfosit (RPL) sebagai Penanda Inflamasi pada Persalinan PrematurAbstrakPendahuluan: Angka kejadian persalinan prematur di Indonesia mencakup 16-18% dari semua kelahiran hidup. Inflamasi atau infeksi dianggap sebagai salah satu penyebab persalinan prematur. Penelitian ini bertujuan untuk menilai peran rasio trombosit/limfosit (PLR) dan rasio neutrofil/limfosit (NLR) sebagai penanda inflamasi pada kelahiran premature.Metode: Penelitian merupakan studi retrospektif cross-sectional. Data dikumpulkan dari rekam medis RSUD Margono Soekarjo periode Januari 2022 - Februari 2023. Didapatkan 150 pasien hamil tunggal dengan rentang usia kehamilan 28 hingga kurang dari 37 minggu yang terbagi dalam tiga kelompok: kelahiran prematur tanpa ketuban pecah dini (KPD), kelahiran prematur dengan KPD, dan ancaman persalinan prematur. Tes ANOVA multivariat digunakan untuk analisis data.Hasil: Terdapat perbedaan nilai NLR yang signifikan secara statistik, terutama pada kelahiran prematur tanpa KPD dibandingkan dengan kelompok lain (nilai p <0,005), sedangkan perbedaan nilai PLR hanya terdapat pada kelahiran prematur dengan dan tanpa KPD. Temuan kami berbeda dengan penelitian sebelumnya yang menunjukkan nilai NLR lebih tinggi pada kelahiran prematur dengan KPD.Kesimpulan: NLR dan PLR berpotensi digunakan sebagai penanda inflamasi yang mengindikasikan peningkatan risiko kelahiran prematur.Kata kunci: NLR, PLR, persalinan prematur